NALAR KRITIS SAYYID AḤMAD AL-GHUMĀRĪ DALAM TAKHRIJ HADIS: KAJIAN KITAB ĤUȘŪL AL-TAFRĪJ BI-UȘŪL AL-TAKHRĪJ - Niken Basuki, Syachrazad; Muhid (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2024)
This article describes the critical reasoning of Sayyid Aḥmad al-Ghumārī in the field of hadith. Al-Ghumārī was a prominent hadith scholar in the early 20th century, but his works in the field of hadith are now beginning to fade. Despite this, al-Ghumārī was the first figure to introduce the method of hadith takhrij. Therefore, this research aims to revisit al-Ghumārī's thoughts in the study of hadith takhrij, focusing on his work Ĥușūl al-Tafrīj bi-Ușūl al-Takhrīj. This study addresses two issues: 1) The critical reasoning of Aḥmad al-Ghumārī in hadith scholarship, and 2) Aḥmad al-Ghumārī's methodology in performing hadith takhrij as outlined in his book Ĥușūl al-Tafrīj bi-Ușūl al-Takhrīj. This research uses a descriptive method and a literature-based approach through qualitative analysis. The final results of this study are: 1) Aḥmad al-Ghumārī's critical reasoning in performing hadith takhrij relies on his own ijtihad and does not adhere to anyone else's views, showcasing his sharp critical reasoning and deep intelligence. 2) Aḥmad al-Ghumārī has two main characteristics in performing hadith takhrij: first, if the hadith contains a complete wording, he refers to musnad books; second, if the hadith is not mentioned according to its wording, he reads, studies, and memorizes it. Those accustomed to performing takhrij can independently distinguish the Prophet's sayings from others.